Sistem Pembelajaran Berbasis Pesantren di Asrama Madrasah Ibtidaiyah Darul Hikmah Purwokerto Barat - Andit Triono; Faizah Nur Atika; Ulfatun Mukaromah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2017)
in the MI Darul Hikmah West Purwokerto’s Boarding School. This program is specified for sixth grade students who will follow National Examination and School Examination. Generally, student will only get specific examination materials without give attention to other aspects in facing an exam. But, it’s different with Darul Hikmah West Purwokerto which implemented the pesantren system in its Boarding School. It’s not only give examination materials but also living skill.The case that considered in this research is how is the pesantren instructional system in MI Darul Hikmah West Purwokerto’s Boarding School. The purpose of this research is to get the description about pesantren instructional system in MI Darul Hikmah West Purwokerto’s Boarding School 2013/2014 Education Year.This is the field research. The research used observation, documentation and interview method. The subjects of this research are the leader of school, dormitory mentor, teachers and students. We used Miles and Huberman data analysis models.The research result shows that Pesantren Instructional System in MI Darul Hikmah West Purwokerto’s Boarding School is the instructional system which adapts the pesantren glorious values. It’s internalized in all of student activities in its boarding school. All of components in this instructional system of the boarding school such as the purpose, the materials, the methods, the learning sources, and the evaluation are likely similar with pesantren learning.